IMPLEMENTASI METODE WEIGHTED PRODUCT WP DALAM PENGEMBANGAN POTENSI KOGNITIF UNTUK MENENTUKAN PROGRAM STUDI DALAM PENERIMAAN MAHASISWA BARU PADA SISWA KELAS XII DI SMK BINTANG NUSANTARA - Indra Kristianto; Ahmad (OKTAL : Jurnal Ilmu Komputer dan Sains, 2024)
The implementation of the Weighted Product (WP) method in developing cognitive potential for determining study programs in admitting new students to class XII students at SMK Bintang Nusantara is an important research topic in the context of increasing the efficiency and accuracy of the process of admitting new students. The purpose of this research is to identify students' cognitive potential and use the WP method as an assessment tool that can help determine the study program that best suits their potential. The literature review describes theories related to the development of cognitive potential, determining study programs, and WP methods. This research method involves identifying variables, developing rating scales, collecting data, calculating weights and rankings, assessing study programs, evaluating and analyzing, as well as validating and correcting. Data were obtained through questionnaires, cognitive potential tests, and structured interviews with class XII students at Bintang Nusantara Vocational School. This research has benefits in increasing the efficiency and accuracy of the new student admissions process and helping class XII students at Bintang Nusantara Vocational School in choosing study programs that suit their cognitive potential. It is hoped that the implementation of this WP method can make a positive contribution to the development of students' cognitive potential and increase their satisfaction with the chosen study program.